Between Adat, Social Practice and Islamic Law: Marital Rights and Obligations of Career Wives in Aceh, Indonesia - Muhazir Muhazir; Mustari Humaira; Nanda Herijal Putra (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2025)
The increasing participation of wives in professional and economic activities has become a significant phenomenon in contemporary Muslim society, including Langsa City. A career wife refers to a married woman who works outside the home to support family income, develop personal potential, and apply her skills and knowledge. This study addresses the issue of how the rights and obligations of career wives are fulfilled in family life and examines these practices from the perspective of fiqh munakahat. This research aims to analyze the implementation of marital rights and obligations toward career wives and to assess their conformity with Islamic family law principles. The study employs a normative-empirical research method. The normative approach examines Qur’anic verses, Hadith, and classical juristic opinions related to fiqh munakahat, while the empirical approach explores social realities through the lens of family sociology within the community of Gampong Paya Bujok Seulamak, Langsa City. The findings indicate that wives’ participation in work is largely driven by the husbands’ insufficient income to meet household needs. However, the practice of financial maintenance (nafkah) often deviates from Islamic legal provisions. Many husbands cease providing nafkah due to the wives’ independent income and higher earnings. Such practices demonstrate a misunderstanding of Islamic legal norms, as fiqh munakahat affirms that the obligation of nafkah remains with the husband regardless of the wife’s employment status. Economic limitations do not nullify this obligation but require adjustment according to the husband’s financial capacity. This study highlights the need for strengthening public understanding of marital responsibilities to ensure household harmony based on Islamic legal principles.